UPAYA MENINGKATKAN KEMAMPUAN ANAK DALAM MENGENAL HURUF MELALUI MEDIA LOOSE PART DI KELAS B TK SADAR BAKTI KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Damerta, Tri Daen; wahyuni, sri; sormin, darliana; lubis, jumaita nopriani (Nunchi : Islamic Parenting Journal, 2023)
Because teachers often use whiteboard media to make students recognize the name of the letter but do not know the letter when asked. The purpose of the study was to see whether through loose part media can improve children's ability to recognize letters.This type of research is a class action research carried out in Class B of TK Sadar Bakti, Sungai Aur District, West Pasaman Regency. Data collection techniques include interviews, observations, and documentation. The study was carried out with III cycles, each cycle 3 meetings. In each cycle has shown an increase in ability in children. The results of research in the first cycle showed an increase in the ability to recognize letters by 40%. Cycle II rose again by 66.67%. Scycle III grew rapidly by 93.33%. Thus, it is concluded that classroom action research using loose part media can improve children's ability to recognize letters.